Contracting Assistance in the Era of Digital Transformation in Algeria. - Ramdani , Kamel; Guetib , Abdelkader (Dirassat Journal Economic Issue, 2024)
This research aims to present the concept of contracting assistance and its essential services. It also explores the concept of digital transformation and outlines its key requirements. The research seeks to assess the reality of contracting assistance in the context of digital transformation in Algeria, relying on indicators of the Arab digital economy. It investigates the mechanisms used to implement contracting assistance by initiating digitization as a preliminary step. Finally, the paper sheds light on some features of digital transformation in the application of contracting assistance through digital platforms and websites. Ultimately, it concludes with a set of important suggestions to contribute to the enhancement of digital transformation, particularly in the field of entrepreneurship.